Interactive Multimedia Exploring Balinese Traditions in Natural and Sosial Science Subjects Culturally Rich Indonesian Material for Class IV Students - Ni Kadek Febry Jelita Wulandari; I Gusti Agung Ayu Wulandari; Ni Luh Putu Agetania (Universitas Pendidikan Ganesha, 2025)
The lack of integration of technology and local culture in learning causes low cultural literacy and student learning outcomes. This research aims to develop interactive multimedia exploring Balinese traditions in science and science subjects, especially the material My Indonesia is Rich in Culture for fourth grade elementary school students. This research includes development research. The ADDIE model used in this research consists of 5 stages, namely Analyze, Design, Development, Implementation, and Evaluation. This research involved content/materials, design, learning media experts, and 14 students. The data collection methods used were questionnaires and tests. Data analysis techniques use quantitative descriptive analysis and inferential statistical analysis (t-test). The media feasibility test results from expert content, design, media, individual trials and small group trials were sequentially 95,4%; 92,5%; 91,6%; 91,6%; 95% is included in the very good category. The results of the effectiveness test using the one sample t-test obtained tcount = 5.63 and ttable = 1.771 at a significance level of 5% with db = 13. These results show tcount > ttable, so H0 is rejected and H1 is accepted. It can be concluded that interactive multimedia exploring Balinese traditions is feasible and effective for use in the natural and social science subject, Culturally Rich Indonesian for class IV students.